2005
DOI: 10.1002/jez.a.233
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid steroid levels and subsequent sex of bovine embryos

Abstract: On the basis of evidence suggesting a maternal involvement in the determination of the sex of the offspring, we took ova at the point of ovulation from crossbred heifers, fertilised them, and established the sex of the embryos. At the same time we took individual-matched samples of follicular fluid from each follicle of origin, and measured the levels of testosterone and oestradiol, blind to the sex of the embryo. We found no effect of oestradiol on sex in either primary or subordinate follicles. But bovine ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…Follicular fluid testosterone levels and subsequent sex of bovine embryos Grant & Irwin (2005) reported that they took ova from bovine follicles and fertilized them in vitro. Each sample of follicular fluid was assayed for testosterone.…”
Section: Splenial Area Of Ratsmentioning
confidence: 99%
“…Follicular fluid testosterone levels and subsequent sex of bovine embryos Grant & Irwin (2005) reported that they took ova from bovine follicles and fertilized them in vitro. Each sample of follicular fluid was assayed for testosterone.…”
Section: Splenial Area Of Ratsmentioning
confidence: 99%
“…Recognising that testosterone underpins a tendency to dominant behaviour (Bouissou 1978, Christiansen 1998, Grant & France 2001, researchers who favoured the maternal dominance hypothesis sought an association between female testosterone and offspring sex ratio (Grant & Irwin 2005, Grant et al 2008, Helle et al 2008, Shargal et al 2008, while those opting for the good condition hypothesis sought links in the area of diet (Rosenfeld et al 2003, Rosenfeld & Roberts 2004, Cameron et al 2008, Mathews et al 2008, and, more explicitly, unsaturated fats , polyunsaturated fatty acids (Fountain et al 2008, Green et al 2008 and glucose (Kimura et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supporting the influence of maternal testosterone on offspring sex ratio Independently, four research teams (Grant & Irwin 2005, Grant et al 2008, Helle et al 2008, Shargal et al 2008, Garcia-Herreros et al 2010 have investigated the hypothesised relationship between pre-conceptual maternal testosterone and the subsequent sex of the offspring. In one study (Shargal et al 2008), the dominant females in a small captive herd of Nubian ibexes were found to have higher faecal testosterone and significantly more male offspring than subordinate females who had lower faecal testosterone and more female offspring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors inferred (from adding methyltestosterone and other hormones to semen of several mammalian species) that offspring sex ratios are hormonally controlled. Recently Grant and her co-workers found that the sex of bovine embryos correlates significantly with pre-ovulatory follicular testosterone concentrations, higher levels being associated with male offspring (Grant & Irwin 2005;Grant et al 2008). Comparable results have been reported in the field vole (Helle et al 2008); rat (Nunez & Juraska 1998) and the ibex (Shargal et al 2008).…”
Section: Accepted Manuscript E Sex-selective Abortiomentioning
confidence: 90%